(3efThQ GdTQW hGdfHWs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje MOhO bGFe GdOjf CjgG GdTjhN GdWgQI bO CYPQ fPjQ GdBNQI hChLH GdMLI Ydi GdCee HGdMce GdeYLRI hGdHQGgjf GdHGgQI s
(3BNQgG (B:s
(3hgh MH YHOg GdVYja GdebJfi ai jhe hjfOe ajg GdeHWdhf hGdTGchf GdPjf BjShG ef QLYJg hdbGFg hbjGeg HSja GdMb hGdYOd Ydi ef Cac Yfg HLMO Mbg hGdBjI JeJ HMeO hdi GdfYeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B100s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis